The Impact of Using a Communicative Approach to Improve Arabic Language Proficiency - Moh. Aziz Arifin; Faisal Mahmud Adam Ibrahim; Umi Machmudah (EDUCATIO : Journal of Education, 2024)
This study aims to examine and analyze the impact of using a communicative approach to improve Arabic language proficiency. The focus is based on the problem of low Arabic speaking skills among students, which, according to the researcher’s hypothesis, is partly due to teachers’ inability to apply appropriate teaching methods that align with learning objectives. This research employed a quantitative method, designed to test the effect of the communicative approach in classroom instruction and its influence on students' Arabic language proficiency. The data source consisted of all Grade XI students, and data analysis was conducted using simple regression with the assistance of SPSS. The results of the analysis revealed: 1) the application of the communicative approach in teaching Arabic language proficiency was categorized as high, with a median score of 84.9, 2) students' Arabic language proficiency was also categorized as high, with a median score of 60.3, and 3) there was a significant effect of 65.2% between the independent variable (X) and the dependent variable (Y), with a significance value of 0.000 and an R square of 0.652.